Springs of western civilization a comparative study of Hebrew and classical cultures - Arieti, James A. (Lexington Books, 2017)
This book explores how the Hebraic and classical traditions forming our Western heritage combined from about 300 BCE to 300 CE. James Arieti investigates the principal causes of the merger in the common model of God that developed in the Greek philosophical schools, along with its ethical implications, and the shared portrayal in biblical, rabbinic, and postclassical literature of the compassionate warm character that we recognize as a mentsh.